A Review of Communication Protocols for Intelligent Remote Terminal Unit Development - Ab Ghani, Mohd Ruddin; Wan Jusoh, Wan Nor Shela Ezwane; Mat Hanafiah, Mohd Ariff; Raman, Siti Hajar; Jano, Zanariah (Universitas Ahmad Dahlan (UAD) and Institute of Advanced Engineering and Science (IAES), 2013)
This paper reviewed all the possible interfacing communication protocols for remote terminal unit (RTU). Supervisory Control and Data Acquisition (SCADA) system is a central station that can communicate with other network using the protocol. Fundamentally, the architectures of all networks are based on the seven layers of open system interconnection (OSI) and International Standard Organization (ISO). The objective of designing the protocols is to check the status of all the input and output field devices and send the report according to that status. The corresponding protocol and communication parameters between the connecting devices will be included in designing a complex SCADA system. The available protocols to develop the communication of RTU are Modbus/ASCII, distribute network protocol(DNP3), controller area network (CAN), International Electro-technical Commission (IEC 60870), and transmission control protocol/internet protocol (TCP/IP).